2016
DOI: 10.1039/c6ce00248j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hierarchical flower-like Bi2MoO6microspheres as efficient photocatalyst for photoreduction of CO2into solar fuels under visible light

Abstract: Hierarchical flower-like Bi 2 MoO 6 microspheres were successfully synthesized via a facile hydrothermal approach, employing PVP as the crystal growth modifier. The building units of the hierarchical flower-like Bi 2 MoO 6 were constructed by two-dimensional thin flakes, which intercrossed with each other and aggregated together to form the three-dimensional flower-like structure. The PVP amount and hydrothermal duration played crucial roles in the formation of the Bi 2 MoO 6 architectures with evolving morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…[179][180][181] It is widely applied in the degradation of organic pollutants [179] and photocatalytic oxygen evolution. [182] Methanol and ethanoly ields were 6.2 and 4.7 mmol h À1 g À1 ,r espectively, which were highert han those reported for hollow Bi 2 WO 6 microspheres. Dai and co-workers found that hierarchical flowerlike Bi 2 MoO 6 exhibited efficient photocatalytic activity for CO 2 conversion.…”
Section: Bi 2 Moomentioning
confidence: 72%
See 1 more Smart Citation
“…[179][180][181] It is widely applied in the degradation of organic pollutants [179] and photocatalytic oxygen evolution. [182] Methanol and ethanoly ields were 6.2 and 4.7 mmol h À1 g À1 ,r espectively, which were highert han those reported for hollow Bi 2 WO 6 microspheres. Dai and co-workers found that hierarchical flowerlike Bi 2 MoO 6 exhibited efficient photocatalytic activity for CO 2 conversion.…”
Section: Bi 2 Moomentioning
confidence: 72%
“…Dai and co-workers found that hierarchical flowerlike Bi 2 MoO 6 exhibited efficient photocatalytic activity for CO 2 conversion. [182] Methanol and ethanoly ields were 6.2 and 4.7 mmol h À1 g À1 ,r espectively, which were highert han those reported for hollow Bi 2 WO 6 microspheres. In 2017, Zhou et al also provedt he photocatalytic activity of Bi 2 MoO 6 for the conversion of CO 2 into CH 4 .…”
Section: Bi 2 Moomentioning
confidence: 72%
“…[3] The g-Bi 2 MoO 6 ,k nown as "koechlinite", [4] is ak ind of visible-light-responsive photocatalyst, widely being applied in the degradation of organic pollutants, [6][7][8][9][10][11][12][13][14][15][16][17][18][19] photocatalytic oxygen evolution, [20][21][22][23] and the photocatalytic reduction of CO 2 . [24] Many g-Bi 2 MoO 6 morphologies were reported,i ncludingn anosheets, nanoplates, flakes or nanobelts, [6][7][8][9][10][11][12][13]20] hollow boxes, [14] nanotubes, [15] hollow spheres, [16,17] nanoparticles, [18] and flowerlike hierarchical microspheres. [19,24] Hierarchicala rchitectures, building of nanorods, nanoplates, nanotubes etc.,h ave received wide attention in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Many g-Bi 2 MoO 6 morphologies were reported,i ncludingn anosheets, nanoplates, flakes or nanobelts, [6][7][8][9][10][11][12][13]20] hollow boxes, [14] nanotubes, [15] hollow spheres, [16,17] nanoparticles, [18] and flowerlike hierarchical microspheres. [19,24] Hierarchicala rchitectures, building of nanorods, nanoplates, nanotubes etc.,h ave received wide attention in photocatalysis. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Properly designed hierarchical structures (including porosity and morphology)c an not only enhance light harvesting and improve molecular diffusion/transportk inetics, but also increase the surface area and the amount of active sites, which accelerate the surface reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation